Assessment of Adult Women With Ovarian Masses and Treatment of Epithelial Ovarian Cancer: ASCO Resource-Stratified Guideline. (2021) - Vanderpuye, Verna D.; Clemenceau, Jean Rene V.; Temin, Sarah; Aziz, Zeba; Burke, William M.; Cevallos, Nixon Leonardo; Chuang, Linus T.; Colgan, Terence J.; del Carmen, Marcela G.; Fujiwara, Keiichi; Kohn, Elise C.; Gonzáles Nogales, Jose Enrique; et al.
Abstract : PURPOSE: To provide expert guidance to clinicians and policymakers in three resource-constrained settings on diagnosis and staging of adult women with ovarian masses and treatment of patients with epithelial ovarian (including fallopian tube and primary peritoneal) cancer. METHODS: A multidisciplinary, multinational ASCO Expert Panel reviewed existing guidelines, conducted a modified ADAPTE process, and conducted a formal consensus process with additional experts. RESULTS: Existing sets of guidelines from eight guideline developers were found and reviewed for resource-constrained settings; adapted recommendations from nine guidelines form the evidence base, informing two rounds of formal consensus; and all recommendations received ≥ 75% agreement. RECOMMENDATIONS: Evaluation of adult symptomatic women in all settings includes symptom assessment, family history, and ultrasound and cancer antigen 125 serum tumor marker levels where feasible. In limited and enhanced settings, additional imaging may be requested. Diagnosis, staging, and/or treatment involves surgery. Presurgical workup of every suspected ovarian cancer requires a metastatic workup. Only trained clinicians with logistical support should perform surgical staging; treatment requires histologic confirmation; surgical goal is staging disease and performing complete cytoreduction to no gross residual disease. In first-line therapy, platinum-based chemotherapy is recommended; in advanced stages, patients may receive neoadjuvant chemotherapy. After neoadjuvant chemotherapy, all patients should be evaluated for interval debulking surgery. Targeted therapy is not recommended in basic or limited settings. Specialized interventions are resource-dependent, for example, laparoscopy, fertility-sparing surgery, genetic testing, and targeted therapy. Multidisciplinary cancer care and palliative care should be offered. Additional information can be found at www.asco.org/resource-stratified-guidelines . It is ASCO's view that health care providers and health care system decision makers should be guided by the recommendations for the highest stratum of resources available. The guideline is intended to complement but not replace local guidelines.